Nearshore and offshore comparison of marine water quality variables measured during SESMA 1 - Wei Bong, Chui,; Weng Lee, Choon, (Malaysian Journal of Science, 2008)
Total suspended solids (TSS), dissolved oxygen (DO) and dissolved inorganic nutrient concentrations [ammonium (NH4), nitrite (NO2), nitrate (NO3), phosphorus (PO4) and silicate (SiO4)] were measured in offshore sites covered by the first Scientific Expedition to the Straits of Malacca or SESMA 1 cruise. Both TSS and DO showed striking differences between nearshore and offshore sites. TSS was elevated nearshore (> 250 mg l-1) but was < 100 mg l-1 offshore. DO was at healthy levels (> 300 ÂµM or 9.6 mg l-1) offshore but were low and sometimes exhibited hypoxia (< 125 ÂµM or 4 mg l-1) nearshore. Dissolved inorganic nutrients were generally higher nearshore and this reflected eutrophication. High TSS, low DO and eutrophication showed that anthropogenic activities are affecting the marine water quality in Malaysia